Analyzing financial performance of Tunisian Banks using Financial Ratios - Hamdani, Hanene (Journal of Ecohumanism, 2025)
Purpose: This paper assesses financial performance of Tunisian banks during the period 2010-2020. Design/methodology/approach: The sample is composed by 10 banks observed over the period 2011-2020. We used the conventional/financial ratio approach to assess the financial performance. Findings: The results obtained stated that the level of profitability of the Islamic bank Al Baraka (TIBAB) is lower than the nine conventional banks introduced in this study. The liquidity analysis reveals that TIBAB seems to be statistically more liquid than those of conventional banks. In terms of solvency, TIBAB seems to be less risky and more solvent than other banks. Other measures also showed a risk of deterioration, but are not statistically significant. This implies that the TIBAB is much more liquid and therefore is exposed to a lower liquidity risk than conventional ones. Originality/Value: The originality stems from the examination of historical trends over a series of years covering the transitional period and the impact of COVID-19 in 2020, allowing the conduction of an analysis over specific periods.